2019
DOI: 10.36957/jai.2182-696x.v8i3-1
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of laughter-inducing and humor nursing interventions in people undergoing hemodialysis

Abstract: Benefícios das intervenções de enfermagem indutoras do riso e do humor em pessoas submetidas a hemodiáliseBenefits of laughter-inducing and humor nursing interventions in people undergoing hemodialysis Beneficios de las intervenciones de enfermería que provocan la risa y el humor en personas sometidas a hemodiálisis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…One study found that laughter therapy was effective in reducing pain in hemodialysis patients (Ozer, 2019). In a previous systematic review on the subject, similar therapy was reported to be effective in reducing pain in hemodialysis patients (Macedo et al, 2019). In Journal of Public Health Nursing E. Üner, A. Sezer Balcı, H. Kadıoğlu 264 one study in this systematic review, laughter therapy was less effective in reducing blood sugar levels in individuals with diabetes.…”
Section: Discussion Of the Effects Of Laughter Therapy On Physical He...mentioning
confidence: 64%
See 1 more Smart Citation
“…One study found that laughter therapy was effective in reducing pain in hemodialysis patients (Ozer, 2019). In a previous systematic review on the subject, similar therapy was reported to be effective in reducing pain in hemodialysis patients (Macedo et al, 2019). In Journal of Public Health Nursing E. Üner, A. Sezer Balcı, H. Kadıoğlu 264 one study in this systematic review, laughter therapy was less effective in reducing blood sugar levels in individuals with diabetes.…”
Section: Discussion Of the Effects Of Laughter Therapy On Physical He...mentioning
confidence: 64%
“…In this systematic review, laughter therapy was found to be less effective in reducing blood pressure levels in university students. Study, it was reported that the therapy was effective in reducing blood pressure in hemodialysis patients (Macedo et al, 2019). Although it is stated in the literature that it is effective in different samples, this effect should be tested in university students.…”
Section: Discussion Of the Effects Of Laughter Therapy On Physical He...mentioning
confidence: 97%
“…34 A study conducting LY with hemodialysis patients, reported that the therapy was effective in lowering blood pressure in hemodialysis patients. 35 Studies have shown that there is limited evidence about the effect of LY on physiological parameters, especially measurements such as blood pressure, heart rate, and oxygen saturation, which need to be investigated in less studied sample groups such as university students. It is important to reduce the stress experienced by nursing students during the pandemic and to increase their happiness, strengthen their positivity and ensure their health.…”
Section: Discussionmentioning
confidence: 99%